A Novel Navigation Device for Precise Percutaneous Placement of the Guidewire in Femoral Neck Fracture Cannulated Screw Fixation Surgery - Yutao Cui; Guangkai Ren; Chuangang Peng; Baoming Yuan; Dankai Wu (IEEE Journal of Translational Engineering in Health and Medicine, 2024)
The accuracy of screw placement is a key factor for the stability of the cannulated screws used in the fixation of femoral neck fractures. In this study we designed a navigation device for ensuring the screw reaches the ideal position for optimal fixation. From March 2019 to September 2020, 66 patients with femoral neck fracture were enrolled and divided into 2 groups, one group was treated using the traditional free-hand cannulated screw fixation and the other using the new navigation device with assisted fixation. The effectiveness of the 2 methods was compared based on surgery duration, intraoperative bleeding, number of fluoroscopic examination and guidewire insertion attempts, screw parallelism, and effective fixation area. Fracture healing, complications and hip joint function were assessed after operation. The new navigation device reduced the duration of surgery without causing additional intraoperative bleeding, and significantly reduced number of fluoroscopy examination and guidewire insertion attempts (4.00±1.58 vs. 6.09±1.94 with traditional surgery). The accuracy of screw implantation was improved, as demonstrated by increased screw parallelism (0.71±0.57° vs. 1.66 ±1.01° with traditional surgery) and higher effective fixed area (64.88±10.52 vs. 58.61±9.19 mm2 with traditional surgery). In the postoperative follow-up, except for one case of femoral head necrosis and one case of bone nonunion in the traditional surgical group, the other patients showed fracture healing. There was no significant difference in hip joint function between the 2 groups. The new navigation device enables rapid and accurate guidewire positioning for cannulated screw fixation through simple operation procedures, resulting in good prospect for clinical transformation.